INTERNAL DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN TAMBANG BATUBARA DI BURSA EFEK INDONESIA - Suastawa, I Gede; Candraningrat, Ica Rika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Companies in carrying out operations and developing business certainly require capital and additional capital. The purpose of this study was to determine the internal determinants of capital structure. This research was conducted on coal mining sub-sector companies on the Indonesia Stock Exchange for the period 2016 – 2020. In this study, five independent variables were used, namely profitability, company size, liquidity, non-debt tax shield, and company growth, while the dependent variable was structure capital. The sample used was determined by purposive sampling method and obtained 22 companies as a sample of a total of 24 listed companies. The data in this study were collected using the non-participant observation method by making observations on the company's financial statements. The data analysis technique used is multiple linear regression analysis. The results of multiple linear regression analysis show that profitability and liquidity have a significant negative effect on capital structure, firm size and firm growth have a significant positive effect on capital structure, but the non-debt tax shield variable does not have a negative effect on capital structure.